Evaluation of vocal-electronic nursing documentation: A comparison study in Iran. (3rd July 2017) - Mohammadi Firouzeh, Mona; Jafarjalal, Ezzat; Emamzadeh Ghasemi, Hormat Sadat; Bahrani, Naser; Sardashti, Sara
ABSTRACT: Aim: Documentation is a critical element in the function of the nursing team, and cannot be separated from high-quality, patient-centered care. The aim of this study was to compare the quality of nursing documentation in electronic and paper-based systems. Method: A retrospective descriptive study was designed to compare the quality of nursing documentation in electronic health records (EHR) versus paper-based documentation systems before and after the application of the electronic system. Results: Analysis of data found a significant difference in the quality of nursing documentation in the two hospitals both before and after the implementation of an EHR system ( p < 0.001).Quality of nursing documentation in the electronic system was significantly better than that of paper-based documentation systems. Conclusion: Vocal-electronic systems help to improve quality of nursing documentation, suggesting this aspect may be essential to implementing a successful system in local settings.